Causal factors of nano marketing strategy affecting the consumer repurchase behavior in cosmetic business - Virochpoka, Rungpol; U-on, Vichit (Edelweiss Applied Science and Technology, 2025)
The cosmetics industry is one that manufactures and sells cosmetic products, with efforts to expand brand recognition and production through influencers on social media. The heavy promotion of these products on social media accounts has made influencers an important marketing platform for cosmetic brands. However, brands must invest time and effort in finding the right influencers for their campaigns. Marketing mistakes made by influencers can result in unnecessary costs, difficulty in measuring outcomes, or pose high risks for the brand. The objectives of this research study were: 1) to study the causal factors affecting nano-marketing strategy and consumer repurchase behavior in the cosmetic business, 2) to study the influence of causal factors of nano-marketing strategy affecting consumer repurchase behavior in the cosmetic business, and 3) to develop a model of the causal factors of nano-marketing strategy affecting consumer repurchase behavior in the cosmetic business. A researcher collected data from interviews and online questionnaires with the cosmetic business, from July 2024 to September 2024, by collecting a sample of 560 people. The results of the analysis concluded that the microenvironment affected the nano-marketing strategy, the microenvironment affected consumer repurchase behavior through the nano-marketing strategy, community influencers affected the nano-marketing strategy, community influencers affected consumer repurchase behavior through the nano-marketing strategy, social media networking affected the nano-marketing strategy, social media networking affected consumer repurchase behavior through the nano-marketing strategy, and the nano-marketing strategy affected consumer repurchase behavior. The cosmetics business can develop plans in terms of the microenvironment, influencers within specific groups, and social media networking, allowing the cosmetics business to identify the nano-marketing strategy and consumer repurchase behavior. This approach also enables the business to respond to its own needs and implement processes for making purchasing decisions.